Identifikasi Jamur Pada Terigu Yang Dijual Tanpa Merek di Pasar Besar Kota Palangka Raya - Alifia Banjarani; Agnes Immanuela Toemon; Natalia Sri Martani; Arif Rahman Jabal; Dian Mutiasari (Direktorat Politeknik Kesehatan Makassar, 2024)
Good food is food that does not contain dangerous ingredients and meets hygiene and sanitation standards, however BPOM stated that distributor buildings and retail facilities were found that stored damaged, expired and illegal food ingredients, one of which was damaged wheat flour due to fungal contamination originating from wheat grains/seeds. Wheat flour that is at high risk of being contaminated with mold is wheat flour that is sold without a brand and uses thin, transparent plastic, making it easier for air containing mold spores to enter. To determine the presence of mold and identify the species of mold found in wheat flour sold without a brand at Pasar Besar Palangka Raya City. This type of research uses descriptive methods with a cross sectional design. The research population consisted of 41 wheat flours sold without brands at Pasar Besar Palangka Raya City, with a sampling technique using purposive sampling based on inclusion and exclusion criteria. The research instrument used was a microscope. Data processing techniques include coding, tabulating, entering, editing, and cleaning with univariate analysis techniques (descriptive analysis) and using percentage formulas. The results of examining 41 wheat flour samples and identifying fungi using SDA (Sabouraud Dextrose Agar) media showed that the percentage was 100% positive for contamination with Aspergillus spp. The results obtained from this research were that all (100%) wheat flour samples were positively contaminated with Aspergillus spp.